A Sephardi Sea: Jewish memories across the modern Mediterranean - Miccoli, Dario (Sephardi and Mizrahi studies, 2022)
Acknowledgments -- Note on transliteration -- Introduction: Being Jewish in the Mediterranean -- Writing exile: Sephardi and Mizrahi literary memories -- (In)tangible heritages: migrant associations, museums, and the internet -- An unfinished present: migrations of Sephardi and Mizrahi memory -- Conclusion: Afterlives of exile -- References -- Index.